Enter a problem...
Calculus Examples
cos(2y)=xcos(2y)=x
Step 1
Differentiate both sides of the equation.
ddx(cos(2y))=ddx(x)ddx(cos(2y))=ddx(x)
Step 2
Step 2.1
Differentiate using the chain rule, which states that ddx[f(g(x))]ddx[f(g(x))] is f′(g(x))g′(x) where f(x)=cos(x) and g(x)=2y.
Step 2.1.1
To apply the Chain Rule, set u as 2y.
ddu[cos(u)]ddx[2y]
Step 2.1.2
The derivative of cos(u) with respect to u is -sin(u).
-sin(u)ddx[2y]
Step 2.1.3
Replace all occurrences of u with 2y.
-sin(2y)ddx[2y]
-sin(2y)ddx[2y]
Step 2.2
Differentiate using the Constant Multiple Rule.
Step 2.2.1
Since 2 is constant with respect to x, the derivative of 2y with respect to x is 2ddx[y].
-sin(2y)(2ddx[y])
Step 2.2.2
Multiply 2 by -1.
-2sin(2y)ddx[y]
-2sin(2y)ddx[y]
Step 2.3
Rewrite ddx[y] as y′.
-2sin(2y)y′
-2sin(2y)y′
Step 3
Differentiate using the Power Rule which states that ddx[xn] is nxn-1 where n=1.
1
Step 4
Reform the equation by setting the left side equal to the right side.
-2sin(2y)y′=1
Step 5
Step 5.1
Divide each term in -2sin(2y)y′=1 by -2sin(2y).
-2sin(2y)y′-2sin(2y)=1-2sin(2y)
Step 5.2
Simplify the left side.
Step 5.2.1
Cancel the common factor of -2.
Step 5.2.1.1
Cancel the common factor.
-2sin(2y)y′-2sin(2y)=1-2sin(2y)
Step 5.2.1.2
Rewrite the expression.
sin(2y)y′sin(2y)=1-2sin(2y)
sin(2y)y′sin(2y)=1-2sin(2y)
Step 5.2.2
Cancel the common factor of sin(2y).
Step 5.2.2.1
Cancel the common factor.
sin(2y)y′sin(2y)=1-2sin(2y)
Step 5.2.2.2
Divide y′ by 1.
y′=1-2sin(2y)
y′=1-2sin(2y)
y′=1-2sin(2y)
Step 5.3
Simplify the right side.
Step 5.3.1
Separate fractions.
y′=1-2⋅1sin(2y)
Step 5.3.2
Convert from 1sin(2y) to csc(2y).
y′=1-2csc(2y)
Step 5.3.3
Move the negative in front of the fraction.
y′=-12csc(2y)
Step 5.3.4
Combine csc(2y) and 12.
y′=-csc(2y)2
y′=-csc(2y)2
y′=-csc(2y)2
Step 6
Replace y′ with dydx.
dydx=-csc(2y)2